STRATEGI PENGEMBANGAN USAHA PADA CV WIRAMITRA KABUPATEN SIDOARJO - Lailatul Fajriyah; Titin Kartini (Economic Education, University of Jember, 2015)
Business development strategy is a way to make an effort to become more advanced, better, and focus on long-term goals in a competitive state of the company. This study aimed to describe the business development strategies undertaken by CV Wiramitra Sidoarjo. This type of research used is descriptive qualitative approach. The place of this research is determined by using purposive method implemented in the CV Wiramitra area located at Ciputran Perum Citra Garden B 07/09 Sidoarjo, East Java. Analysis of the data in this study consisted of data reduction, data presentation, and conclusion. Based on the research results, it can be seen that the CV Wiramitra Sidoarjo is a service company servers by implementing several business development strategy in operation. The business development strategies undertaken by CV Wiramitra include: product development, market penetration, and market development.